The Development of Classification System of Student Final Assignment Using Naive Bayes Classifier Case Study: State Community Academy of Bojonegoro - Yoga Saputra, Pramana; Yunhasnawa, Yoppy; Fatmila, Windy; Rahutomo, Faisal; Andrie Asmara, Rosa; Wahyu Wibowo, Dimas; Rohadi, Erfan; Siradjuddin, Indrazno; Setiawan, Awan; Hafidh Ayatullah, Ahmad; Rahmad Syulistyo, Arie; Cahyandari, Dewi; et al. (International Journal of Engineering and Technology, 2018)
In determining interest, students are faced with the choice of specialization in determining the final field of interest. Specialization in the Information Management Study Program of State Community Academy of Bojonegoro is divided into five specializations. The choice of specialization groups is an important part. This is because the accuracy in choosing specialization groups is part of the initial plan of students to determine the final assignment project. Thus, the field of specialization taken will be in accordance with the interests and abilities of the students and will have an impact on the process. In this work, we propose a system that can provide information about the classification of student final assignments. We use Naive Bayes Classifier (NBC) algorithm to do the classification. In this work, we used datasets, that obtained from the State Community Academy of Bojonegoro Informatics Management Study Program. Based on the accuracy testing of the classification results, the system gives higher result, than test manual calculation of 83.33%.Â Â